2007
DOI: 10.1074/jbc.m704428200
|View full text |Cite
|
Sign up to set email alerts
|

The RAS-dependent ERF Control of Cell Proliferation and Differentiation Is Mediated by c-Myc Repression

Abstract: The ERF transcriptional repressor is a downstream effector of the RAS/ERK pathway that interacts with and is directly phosphorylated by ERKs ETS2-repressor factor (ERF)3 is a ubiquitously expressed transcriptional regulator of the ETS family of transcription factors, with tumor suppressor activity, that is regulated by the RAS/ERK signaling pathway. ERF is shown to be bound and phosphorylated both in vivo and in vitro by ERKs (1, 2). It interacts specifically with active and inactive ERKs via two distinct FXF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 64 publications
1
30
1
3
Order By: Relevance
“…Erf and Etv3 are cell cycle inhibitors in certain cell types (Klappacher et al, 2002;Sawka-Verhelle et al, 2004;Sgouras et al, 1995;Verykokakis et al, 2007). Since RARs act early in the neuronal differentiation pathway, we hypothesized that ERF and ETV3/3L might act downstream of RARs to promote cell cycle exit and increase neuronal differentiation.…”
Section: Erf or Etv3/3l Knockdown Expands Expression Of Neural Progenmentioning
confidence: 99%
“…Erf and Etv3 are cell cycle inhibitors in certain cell types (Klappacher et al, 2002;Sawka-Verhelle et al, 2004;Sgouras et al, 1995;Verykokakis et al, 2007). Since RARs act early in the neuronal differentiation pathway, we hypothesized that ERF and ETV3/3L might act downstream of RARs to promote cell cycle exit and increase neuronal differentiation.…”
Section: Erf or Etv3/3l Knockdown Expands Expression Of Neural Progenmentioning
confidence: 99%
“…It seems that multiple mechanisms are controlling the expression, activity, and subcellular localization of ERF, which highlight its physiologic significance in the cell. Recently, ERF was suggested to impose repression checkpoints on a subset of cell cycle control genes (26,27). We have shown that cyclin A, a key factor in the cell Figure 4.…”
Section: Egfr Downregulates Erf Through Mir-7 Inductionmentioning
confidence: 99%
“…ETV3 was identified as an anti-proliferative factor induced during macrophage differentiation [186,188] and neuronal differentiation [22]. ERF mediates the switch between proliferation and differentiation in macrophages, fibroblasts, extraembryonic ectoderm, and neuroectoderm [22, 167,187,189]. Importantly, both Erf and Etv3 are upregulated by RAR agonists, down-regulated by RAR antagonists, and knockdown of ERF or ETV3 results in paralysis, loss of primary neurons and increased proliferation of undifferentiated neural progenitors.…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…The direct targets of ERF repression in neurogenesis are currently unknown. However, since Myc has been identified as an ERF target in fibroblasts [167], it is likely that ERF would also repress n-Myc, a gene that is functionally interchangeable with c-Myc [168]. n-Myc promotes expansion of neural progenitor populations, and would be a good candidate to be repressed by ERF to foster differentiation [169].…”
Section: Neuronal Differentiation and Cell Cycle Genesmentioning
confidence: 99%